Obstetrical and neonatal outcomes among pregnancies complicated by hyperparathyroidism. (31st December 2023) - Trahan, Marie-Julie; Antinora, Christina; Czuzoj-Shulman, Nicholas; Benjamin, Alice; Abenhaim, Haim A.
Abstract: Purpose: Severe hypercalcemia resulting from hyperparathyroidism may result in adverse perinatal outcomes. The objective of this study was to evaluate maternal and neonatal outcomes among pregnant women with hyperparathyroidism using a population database. Methods: A retrospective cohort study was conducted using data from the Healthcare Cost and Utilization Project-Nationwide Inpatient Sample from 1999–2015. ICD-9 codes were used to identify women diagnosed with hyperparathyroidism during pregnancy. Perinatal outcomes between pregnant women with and without hyperparathyroidism were compared. Multivariate logistic regression, controlling for age, race, income, insurance type, hospital location, and comorbidities, evaluated the effect of hyperparathyroidism on perinatal outcomes. Results: Of 13, 792, 544 deliveries included over the study period, 368 were to women with hyperparathyroidism. The overall incidence of hyperparathyroidism was 2.7/100, 000 births, increasing from 1.6 to 5.2/100, 000 births over the study period ( p < 0.0001). Women with hyperparathyroidism were older and had more comorbidities, such as obesity, and pre-gestational hypertension and diabetes. Relative to the comparison group, women with hyperparathyroidism were more likely to deliver preterm, OR 1.69 (95% CI 1.24–2.29), to develop preeclampsia, 3.14 (2.30–4.28), and to deliver by cesarean, 1.69 (1.36–2.09). Infants born to mothers with hyperparathyroidism were more likely to be growth restricted, 1.83 (1.08–3.07), and to be diagnosed with a congenital anomaly, 4.21 (2.09–8.48). Conclusion: Hyperparathyroidism during pregnancy is associated with a significant increase in adverse perinatal outcomes, including preeclampsia, preterm delivery, fetal growth restriction, and congenital anomalies. As such, pregnancies among women with hyperparathyroidism should be considered high-risk, and specialized care is recommended in order to minimize maternal and neonatal morbidity.